Feasibility of high-resolution continuum source molecular absorption spectrometry for vanadium determination. Issue 2 (18th January 2023) - Kowalewska, Zofia; Abad, Carlos; Okruss, Michael; Recknagel, Sebastian
Abstract : This work aimed to evaluate high-resolution continuum source molecular absorption spectrometry (HR-CS MAS), traditionally used to determine non-metals, for the determination of a new element, metal, vanadium. Abstract : This work aimed to evaluate high-resolution continuum source molecular absorption spectrometry (HR-CS MAS), traditionally used to determine non-metals, for the determination of a new element, metal, vanadium. VO was selected as a target molecule because it is relatively stable and was expected to be spontaneously generated in a flame or a graphite furnace (GF). The high-resolution overview spectra of the molecule were obtained in a wide range of 480–630 nm, and absorption due to the X 4 Σ − –C 4 Σ − electronic transition was registered. A unique instrumental setup, comprising a prototype Modular Simultaneous Echelle Spectrograph (MOSES) and a commercial HR-CS MAS apparatus, was applied in the research. Finally, the spectral area centered at 550.6230 nm was selected for analysis. A method was developed to determine V in solutions of catalysts of heavy petroleum oil hydroprocessing using a commercial HR-CS spectrometer in a flame version. Although sensitivity was relatively poor (characteristic concentration 380 mg L −1 ), an extremely low noise enabled reaching a satisfactory detection limit (20 mg L −1 in solution, i.e. 0.1% m:m in the catalyst). For the first time vanadium was determined using ordinary air-acetylene flame. The obtained results were consistent with the results of atomic absorption spectrometry with N2 O-C2 H2 flame. Unfortunately, only a small population of VO molecules could have been generated in GF measurements. Furthermore, the observed VO molecules appeared only at unfavorably high temperatures. The work shows the potential of HR-CS MAS as a scientific tool for investigating the mechanism of processes occurring in the GF. This work can inspire other research of new analytes for HR-CS MAS.